ANALISIS DETERMINAN PENDAPATAN PROVINSI DI PULAU JAWA PADA TAHUN 2014-2023 - Isnawan, Aksan; Khasanah, Uswatun (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2024)
Regional Original Revenue (PAD) is one of the important parameters in evaluating the economic progress of a region. Increases or decreases in PAD can reflect the current economic conditions. This research aims to determine the influence of unemployment, poverty, regional investment, population size, and regional minimum wage (UMP) on provincial revenue in Java Island. The study was conducted in 6 provinces on Java Island, using secondary data obtained from BPS (Central Statistics Agency) and the Ministry of Finance, and tested using panel data regression. The software Eviews 12 was used for analysis. The results show that poverty, regional investment, population size, and UMP significantly affect regional original revenue, while the unemployment variable does not affect regional original revenue.